2020
DOI: 10.3390/nu13010087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Synbiotic Formula on Functional Bowel Disorders and Gut Microbiota Profile during Long-Term Home Enteral Nutrition (LTHEN): A Pilot Study

Abstract: Long-term enteral nutrition (LTEN) can induce gut microbiota (GM) dysbiosis and gastrointestinal related symptoms, such as constipation or diarrhoea. To date, the treatment of constipation is based on the use of laxatives and prebiotics. Only recently have probiotics and synbiotics been considered, the latter modulating the GM and regulating intestinal functions. This randomized open-label intervention study evaluated the effects of synbiotic treatment on the GM profile, its functional activity and on intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The Fe concentration reaching the colon will be higher since the diet Fe amount is higher (14) and may affect the microbiome composition. This alteration, known as dysbiosis, is responsible for the adverse effects observed as inflammation (15)(16)(17) and diarrhoea (18)(19)(20) .…”
Section: Iron Supplement Drinking Water Sewagementioning
confidence: 99%
“…The Fe concentration reaching the colon will be higher since the diet Fe amount is higher (14) and may affect the microbiome composition. This alteration, known as dysbiosis, is responsible for the adverse effects observed as inflammation (15)(16)(17) and diarrhoea (18)(19)(20) .…”
Section: Iron Supplement Drinking Water Sewagementioning
confidence: 99%
“…Previous studies have shown that the abundance of specific species among intestinal bacteria differs in patients with constipation. People with symptoms of constipation reportedly have decreased abundance of Bifidobacteria and Lactobacillus and increased abundance of Bacteroidetes compared to the general population ( D’Onofrio et al, 2020 ; Wang et al, 2020 ). Such changes in the intestinal microbiota affect intestinal motility and intestinal environment ( Zhao and Yu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%